2019
DOI: 10.3389/fnmol.2019.00065
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone in Glioblastoma Multiforme Therapy: Mechanisms and Controversies

Abstract: Glioblastoma multiforme (GBM) is the most common and malignant of the glial tumors. The world-wide estimates of new cases and deaths annually are remarkable, making GBM a crucial public health issue. Despite the combination of radical surgery, radio and chemotherapy prognosis is extremely poor (median survival is approximately 1 year). Thus, current therapeutic interventions are highly unsatisfactory. For many years, GBM-induced brain oedema and inflammation have been widely treated with dexamethasone (DEX), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 166 publications
(212 reference statements)
1
61
0
1
Order By: Relevance
“…Several studies suggest a detrimental effect of dexamethasone on GBM survival outcomes. 27 Although available data are inconclusive and mainly retrospective with inherent bias, steroids should be used as needed but with caution during the SARS-CoV-2 pandemic. A recent publication outlined the detrimental effects and the clinical outcomes of corticosteroid use in coronavirus and similar outbreaks as a reference.…”
Section: Steroidsmentioning
confidence: 99%
“…Several studies suggest a detrimental effect of dexamethasone on GBM survival outcomes. 27 Although available data are inconclusive and mainly retrospective with inherent bias, steroids should be used as needed but with caution during the SARS-CoV-2 pandemic. A recent publication outlined the detrimental effects and the clinical outcomes of corticosteroid use in coronavirus and similar outbreaks as a reference.…”
Section: Steroidsmentioning
confidence: 99%
“…Using mouse GBM models, we determined that surgical resection alone leads to a reduction in circulating T cells, in addition to the known impact of steroid treatment [18][19][20] , which is also being revisited in terms of its clinical use. Many groups have shown that T cell abundance is one of multiple factors influencing immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…Our search on drugs used in glioma treatment revealed that Bevacizumab is monoclonal antibody which targets the VEGF pathway via its downstream cascade of PI3K pathway. Also, FGFR2, MAP2K2, MAP3K4, and HSPB1, which are targets to Dexamethasone, are associated with "Regulation of actin cytoskeleton" and "GnRH signaling pathway" (Cenciarini et al, 2019). The study of the drugs, drug targets, and their associated pathway is particularly important to understand what features of cancer can be utilized for treatment.…”
Section: Involvement Of Identified Significant Genes On Different Pmentioning
confidence: 99%